2020
DOI: 10.3390/molecules25102268
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkyl-2-[4-(trifluoromethyl)benzoyl]hydrazine-1-carboxamides and Their Analogues: Synthesis and Multitarget Biological Activity

Abstract: Based on the isosterism concept, we have designed and synthesized homologous N-alkyl-2-[4-(trifluoromethyl)benzoyl]hydrazine-1-carboxamides (from C1 to C18) as potential antimicrobial agents and enzyme inhibitors. They were obtained from 4-(trifluoromethyl)benzohydrazide by three synthetic approaches and characterized by spectral methods. The derivatives were screened for their inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) via Ellman’s method. All the hydrazinecarboxamides reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The hydrazide–hydrazones 2 and 3 as well as the parent compound 1 were screened for their potential to affect the function of AChE isolated from electric eel ( Ee AChE) and BuChE obtained from equine serum (EqBuChE) using Ellman’s spectrophotometric method ( Table 1 ). These enzymes of nonhuman origin were used to screen inhibitory activity and to compare the results with our previous compounds sharing a certain degree of a chemical similarity [ 23 , 24 ]. Their efficacy is expressed as the concentration leading to 50% inhibition of the enzymatic activity (IC 50 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrazide–hydrazones 2 and 3 as well as the parent compound 1 were screened for their potential to affect the function of AChE isolated from electric eel ( Ee AChE) and BuChE obtained from equine serum (EqBuChE) using Ellman’s spectrophotometric method ( Table 1 ). These enzymes of nonhuman origin were used to screen inhibitory activity and to compare the results with our previous compounds sharing a certain degree of a chemical similarity [ 23 , 24 ]. Their efficacy is expressed as the concentration leading to 50% inhibition of the enzymatic activity (IC 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between 4-hydroxybenzohydrazide-hydrazones and laccase from Trametes versicolor was studied and a competitive type of inhibition was identified [ 22 ]. In our previous study [ 23 ], N -alkyl-2-[4-(trifluoromethyl)benzoyl]hydrazine-1-carboxamides were identified as inhibitors of both AChE and BuChE. Based on here presented findings, we investigated our trifluoromethylated hydrazide–hydrazones 2 – 3 ( Table 1 ) [ 12 ] as potential inhibitors of AChE a BuChE together with their newly prepared analogues 2n – 2u .…”
Section: Introductionmentioning
confidence: 99%
“…2-Acylhydrazine-1-carboxamides are a group of compounds with interesting and potentially useful biological properties utilized in drug design. They have been reported as antimycobacterial [ 1 , 2 ], antibacterial [ 3 , 4 ], antifungal [ 4 ], anticancer [ 5 ], anticonvulsant [ 6 ] and anti-inflammatory [ 3 ] agents. Importantly, hydrazine-1-carboxamides have also been reported as inhibitors of cholinesterases [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have been reported as antimycobacterial [ 1 , 2 ], antibacterial [ 3 , 4 ], antifungal [ 4 ], anticancer [ 5 ], anticonvulsant [ 6 ] and anti-inflammatory [ 3 ] agents. Importantly, hydrazine-1-carboxamides have also been reported as inhibitors of cholinesterases [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation